Nanoparticle‐Programmed Self‐Destructive Neural Stem Cells for Glioblastoma Targeting and Therapy. Issue 24 (21st July 2013) - Cheng, Yu; Morshed, Ramin; Cheng, Shih‐Hsun; Tobias, Alex; Auffinger, Brenda; Wainwright, Derek A.; Zhang, Lingjiao; Yunis, Catherine; Han, Yu; Chen, Chin‐Tu; Lo, Leu‐Wei; Aboody, Karen S.; et al.
<x xml:space="preserve">Abstract</x> A 3‐step glioblastoma‐tropic delivery and therapy method using nanoparticle programmed self‐destructive neural stem cells (NSCs) is demonstrated in vivo: 1) FDA‐approved NSCs for clinical trials are loaded with pH‐sensitive MSN‐Dox; 2) the nanoparticle conjugates provide a delayed drug‐releasing mechanism and allow for NSC migration towards a distant tumor site; 3) NSCs eventually undergo cell death and release impregnated MSN‐Dox, which subsequently induces toxicity towards surrounding glioma cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>